Certification of Quality as a Forerunner of Environmental Sustainability Standards Adoption in the Olive Oil Production Industry - Labella, Rocio Carillo; Parras Ro, Manuel; Eva María, Fatiha Fort,; Armenteros, Murgado (European Journal of Sustainable Development, 2017)
Agriculture is one of the sectors which is considered to have the greatest impact on the environment. That is particularly true in the area of olive oil production where the concept of sustainability is gaining a major importance not only for administrations and organisations but also for consumers and olive oil producers. This sector has previously focused on the quality management certified by different standards (ISO 9001, ISO 22000, BRC, and IFS); however, these days some interest in environmental responsibility is being shown. This interest goes beyond what is being enforced by the regulations and we can see this by the implementation of environmental standards such as the ISO 14001 within these companies. In this paper, through the analysis of the adoption processes of the ISO 14001 standard by both cooperatives and non-cooperative companies, we can determine their level of involvement in the environmental sustainability of olive oil production in the province of Jaén (Spain), where 20% of the world’s production is located. To that effect, we have first studied how many of the 330 companies analysed have adopted the ISO 14001 standard and secondly, qualitative research has been carried out with in-depth interviews involving some of the previously mentioned companies. Results obtained reveal that previous experience of the certification processes ease the adoption of new environmental certifications in such a way that companies which have adopted the ISO 14001 or have stated their intention of doing so possess a high degree of adherence to the ISO 9001 standard. At the same time, they consider that the adoption of that standard makes them more competitive in foreign markets. Keywords: environmental sustainability, ISO 14001, ISO 9001, competitiveness, foreign trade, olive oil